For the love of football? Using economic models of volunteering to study the motives of German football referees - Eike Emrich; Christian Pierdzioch; Christian Rullang (Europäisches Institut für Sozioökonomie e. V., 2016)
Using data for a large sample of German football referees, we studied the motives for becoming a football referee. Based on a long modeling tradition in the literature on the economics of volunteering, we studied altruistic motives (public-goods model) versus non-altruistic (egoistic private-consumption motives and human-capital motives). We differentiated between self-attributed and other-attributed motives. We found that altruistic motives on average are less strong than other motives. Other-attributed altruistic motives are stronger than self-attributed altruistic motives, indicating the presence of a self-interest bias. We further found that referees who report strong altruistic motives have a higher willingness to quit refereeing when other referees would referee more matches, consistent with the public-goods model. In line with the human-capital model, altruistic motives are stronger for senior referees. Altruistic motives are also stronger for those referees who view refereeing as a volunteer activity.
urn:nbn:de:bsz:291-scidok-ds-270384; hdl:20.500.11880/26976
Keywords: 300; socioeconomics of volunteering; survey data; football; motives